COGNITIVE OF STUDENTS IN LANGUAGE EDUCATION DEVELOPING SKILLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, students have been discussed on the tasks carried out in the development of cognitive skills. Students are given examples of the training tasks and assignments used in the organization of independent activities.